2018
DOI: 10.1002/jcp.27416
|View full text |Cite
|
Sign up to set email alerts
|

Homogentisic acid induces morphological and mechanical aberration of ochronotic cartilage in alkaptonuria

Abstract: Alkaptonuria (AKU) is a disease caused by a deficient homogentisate 1,2-dioxygenase activity leading to systemic accumulation of homogentisic acid (HGA), that forms a melanin-like polymer that progressively deposits onto connective tissues causing a pigmentation called "ochronosis" and tissue degeneration. The effects of AKU and ochronotic pigment on the biomechanical properties of articular cartilage need further investigation. To this aim, AKU cartilage was studied using thermal (thermogravimetry and differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Characteristics of AKU cartilage were recently studied using thermal (thermogravimetry and differential scanning calorimetry) and rheological analysis. 51 Drastic changes in thermal and rheological parameters were found, indicating that AKU tissue is not able to enhance chondrocyte metabolism and produce proteoglycans. Consequently, its stiffness drastically rises while dissipative and lubricant roles diminish, manifested also as destruction of the cell-matrix microstructure and disruption of the superficial layer.…”
Section: Understanding the Process Of Ochronosis And Specific Featurementioning
confidence: 98%
See 1 more Smart Citation
“…Characteristics of AKU cartilage were recently studied using thermal (thermogravimetry and differential scanning calorimetry) and rheological analysis. 51 Drastic changes in thermal and rheological parameters were found, indicating that AKU tissue is not able to enhance chondrocyte metabolism and produce proteoglycans. Consequently, its stiffness drastically rises while dissipative and lubricant roles diminish, manifested also as destruction of the cell-matrix microstructure and disruption of the superficial layer.…”
Section: Understanding the Process Of Ochronosis And Specific Featurementioning
confidence: 98%
“…HGA-treated healthy cartilage manifested the same features, indicating that HGA is actually the toxic agent responsible for alterations in cartilage in AKU. 51 There have been some specific features of AKU cartilage described recently. In normal cartilage, collagen fibers were cross-linked covalently to other-type collagen molecules, especially to homotypic polymers of type II collagen, whereas in AKU cartilage high amounts of type III collagen were present.…”
Section: Understanding the Process Of Ochronosis And Specific Featurementioning
confidence: 99%
“…Decades of continuous HGA buildup in patients’ serum, urine, and interstitial fluids are required for alkaptonuria to manifest and result in the characteristic ochronotic pigment deposits primarily found in joints. Cartilage degeneration 33 and SAA amyloid–pigment coaggregations have further been reported 34 .…”
Section: Introductionmentioning
confidence: 93%
“…The amount of OP formed is proportionate to the concentrations of HGA in the medium . ex vivo “organotypic” approaches have modeled AKU by studying the effect of HGA on human cartilage explants . In these studies, pericellular pigmentation of cartilage explants is visible after 2 months of incubation with HGA…”
Section: Formation Of Ochronotic Pigmentmentioning
confidence: 99%
“…Development of these model systems has not only been useful in studying the development of OP under controlled conditions, but also a number of other pathophysiological events closely associated with ochronosis including secondary amyloidosis, perturbed redox homeostasis, and disorder of the cartilage extracellular matrix, including proteoglycan loss and collagen fibril rearrangement . Oxidative stress is a frequent and major consequence of HGA exposure in these studies, as indicated by direct oxidative modification to proteins and depletion of endogenous antioxidants such as glutathione .…”
Section: Formation Of Ochronotic Pigmentmentioning
confidence: 99%